The cinema of Oliver Stone art, authorship and activism - Scott, Ian 1954-; Thompson, Henry (Manchester University Press, 2016)
An insightful study of the master filmmaker's work, enriched by unprecedented access to the director himself
Keywords: Stone, Oliver -- 1946-; Film Theory & Criticism; Individual Film Directors, Film-Makers; PERFORMING ARTS; Film; Stone, Oliver / Criticism and interpretation; Stone, Oliver; Electronic books; Criticism, interpretation, etc